VAVD vacuum may cause bubble transgression in membrane oxygenators. (November 2016) - Nygaard, K; Thiara, AS; Tronstad, C; Ringdal, MA; Fiane, AE
Background: Vacuum-assisted venous drainage (VAVD) is widely used to enhance venous blood return from patients undergoing cardiopulmonary bypass (CPB). This vacuum can accidentally reach the oxygenator of the heart-lung machine and draw gas bubbles into the blood. This is known as bubble transgression (BT) and may cause air emboli in the arterial blood line. In order to avoid BT and minimize the risk of patient injury, knowledge of oxygenator tolerance to vacuum load is critical. Thus, the main aim of this thesis was to investigate how much vacuum a membrane oxygenator can withstand before BT appears. Methods: We investigated four different adult oxygenators: Quadrox-i, Affinity Fusion, Capiox RX25 and Inspire 6M. They were tested in an in vitro setup where VAVD vacuum was allowed to reach the oxygenator through a non-occlusive roller pump. An ultrasonic clinical bubble counter, Gampt BCC 200, was used to count bubbles on the arterial line when the arterial pump was restarted. Results: We observed a significant increase in bubble count for two of the oxygenators, caused by -30 mmHg of VAVD vacuum in the blood reservoir (Affinity Fusion and Inspire 6M). Massive air ingress was shown in two of the oxygenators, caused by -30 mmHg of VAVD vacuum in the reservoir (Capiox RX25) and -40 mmHg of VAVD vacuum in the reservoir (Affinity Fusion). Conclusion: VAVD vacuum may cause bubble transgression in an oxygenator. This was shown for all the oxygenators in this test. VAVD vacuum may cause visible massive air ingress in an oxygenator. This was shown for two of the oxygenators in this test (Capiox RX25 and Affinity Fusion). An alarm triggering on negative pressure in the oxygenator or a pressure relief valve might improve safety when using VAVD.